URGENSI PENGATURAN PENCEGAHAN KEKERASAN SEKSUAL DI LEMBAGA PONDOK PESANTREN - Maulanasyah, Muhammad Rafeillito Hudita; Ahmad, Muh. Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Islamic boarding schools ought to be welcoming and safe environments for both male and female students. On the other side, a number of Islamic boarding schools are under investigation for allegedly committing sexual crimes against their pupils. What's more concerning is that the pesantren's teacher or instructor committed the sexual offense. In addition to realizing a sexual crime prevention model at Islamic Boarding Schools, the goals of this research were to first establish the importance of regulating efforts to prevent sexual violence in Islamic boarding schools. Descriptive analysis and normative legal methodologies were used to perform this study. Based on the study's findings, it was determined that measures to stop sexual violence from Islamic boarding schools could be taken by strengthening state, government, and government oversight of these institutions, providing legal advice on the risks of sexual crimes so that students, particularly female students, could take appropriate action in the event that they were victimized, and creating a sexual crime complaint post at the Institute. Islamic boarding school instruction and Ministry of Religion oversight of Islamic boarding schools